Congestion Management in Deregulated Power System Using FACTS Devices - Arslan Kakajykov, Arslan (Universiti Teknologi Petronas, 2009)
In a deregulated electricity market, it may always not be possible to dispatch all of the contracted power transactions due to congestion of the transmission corridors. Congestion in the transmission lines is one of the technical problems that appears particularly in the deregulated environment. The ongoing power system restructuring requires an opening of unused potentials of transmission system due to environmental, right-of-way and cost problems which are major hurdles for power transmission network expansion. Flexible ac transmission systems devices can be an alternative to reduce the flows in heavily loaded lines, resulting in increased load ability, low system loss, improved stability of the network, reduced cost of production and fulfilled contractual requirement by controlling the power flows in the network. This paper presents the simulation of the powers system with FACTS, using MATLAB SIMULINK and Power System Analysis Toolbox (PSAT).